2005
DOI: 10.1007/s00418-004-0741-6
|View full text |Cite
|
Sign up to set email alerts
|

Localization of TRPC1 channel in the sinus endothelial cells of rat spleen

Abstract: The ultrastructural localization of transient receptor potential C1 (TRPC1) channels in the sinus endothelial cells of rat spleen was examined by confocal laser scanning and electron microscopy. In addition, the localization of the closely associated proteins and channels, VE-cadherin, calreticulin, inositol-1,4,5-trisphosphate receptors type 1 (IP3R1), and ryanodine receptor (RyR), was also examined. Immunofluorescence microscopy of tissue cryosections revealed TRPC1 channels to be localized within the cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…In our study the lack of agonist-, GTP␥S-, or phosphatidylinositol 4,5-bisphosphate depletion-induced currents in TRPC1 overexpressing cells suggests that at least in the heterologous expression system employed by us, TRPC1 proteins per se are unable to form functional homomeric channels in the plasma membrane. This might be explained by their inability for homotetramerization or by intracellular localization of TRPC1 homomers, preventing insertion into the plasma membrane (35)(36)(37). However, at present we cannot rule out that homomeric TRPC1 channels are not gated by typical TRPC activators.…”
Section: Discussionmentioning
confidence: 79%
“…In our study the lack of agonist-, GTP␥S-, or phosphatidylinositol 4,5-bisphosphate depletion-induced currents in TRPC1 overexpressing cells suggests that at least in the heterologous expression system employed by us, TRPC1 proteins per se are unable to form functional homomeric channels in the plasma membrane. This might be explained by their inability for homotetramerization or by intracellular localization of TRPC1 homomers, preventing insertion into the plasma membrane (35)(36)(37). However, at present we cannot rule out that homomeric TRPC1 channels are not gated by typical TRPC activators.…”
Section: Discussionmentioning
confidence: 79%
“…104 Other studies have identified TRPC1 and TRPC4 within the caveolae of rat spleen sinus endothelial cells and mouse interstitial cells of Cajal, respectively. 8,24 Recently, TRPC1 and TRPV6 has been reported to…”
Section: Trp Channels and Caveolaementioning
confidence: 99%
“…In another example, TRPC1 is expressed in the caveolae of rat spleen sinus endothelial cells. 24 Caveolae may only express a limited number of TRP isoforms. 107 Therefore, activation of TRPC1 may be associated with caveolae-related functional changes, such as modulation of endothelial NO synthase and VRAC, but the activation of TRP channels that are not present in the caveolae will have different functional consequences.…”
Section: Convergence and Divergence Of Trp-mediated Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…G protein-coupled receptors (GPCRs), heterotrimeric G proteins, receptor tyrosine kinases, Rho-1, calmodulin, VAMP-2 syntaxin, ezrin, the Na ϩ -H ϩ exchange regulatory factor (NHERF), Z01, Rac-1, stathmin, soluble N-ethylmaleimide-sensitive factor attachment protein receptor proteins, adenylyl cyclase, phosphatidyl inositol-3 kinase, phospholipase C (␤ and ␥), cytoskeletal protein 4, endothelial nitric-oxide synthase, and ion channels are examples of the signaling proteins and molecules known to coexist with caveolin in caveolae (Lockwich et al, 2000;Ostrom et al, 2002;Brazer et al, 2003;Beech, 2005;Cioffi et al, 2005;Ambudkar, 2006;Swaney et al, 2006). Transient receptor potential (TRP) channels have recently been reported to localize within caveolae, particularly the canonical TRPC1, TRPC3, and TRPC4 isoforms (Lockwich et al, 2001;Torihashi et al, 2002;Brazer et al, 2003;Nilius et al, 2003;Uehara, 2005). TRPC1 also coimmunoprecipitates with caveolin-1 (cav-1), one of the three caveolin isoforms (Lockwich et al, 2000;Bergdahl et al, 2003), even more suggestive that it exists within caveolae.…”
mentioning
confidence: 99%